A g-C3N4-loaded platinum-based bimetallic catalytic composite material and preparation method thereof

The preparation of g-C3N4-loaded platinum-based bimetallic catalytic composite material was solved by electrogenerating high-temperature impact processing, and the problems of low catalytic activity of g-C3N4 and low cost and efficiency of modification methods were achieved, and the photocatalytic decomposition of water was achieved with low cost and high efficiency. Hydrogen production.

CN118204111BActive Publication Date: 2024-12-17GUANGDONG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410243816.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2024-12-17
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

The g-C3N4 catalyst has poor charge transport characteristics and low electron-hole recombination rate, which limits its catalytic activity. The existing modification methods are costly and inefficient, making it difficult to quickly and efficiently prepare highly efficient catalytic materials.

Method used

The g-C3N4-loaded platinum-based bimetallic catalytic composite material was prepared by electrophoretic high-temperature impact processing method. The pure g-C3N4 powder was obtained through the first processing, and the second processing was carried on the g-C3N4 powder and another metal atom. , using the synergistic action of bimetal atoms to improve catalytic activity and reduce the load of precious metals.

Benefits of technology

Low-cost and high-efficiency photocatalytic decomposition of water to produce hydrogen is achieved, which improves catalytic activity, broadens the catalytic site, reduces energy consumption, and improves the stability and scope of application of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118204111B_ABST
    Figure CN118204111B_ABST
Patent Text Reader

Abstract

The invention discloses a g-C3N4-loaded platinum-based bimetallic catalytic composite material and a preparation method thereof. The preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material comprises: preparing a metal platinum precursor solution, a metal salt dispersion and a thick mixture, and preparing g-C3N4 powder by electro-induced high temperature impact processing and electro-induced high temperature impact processing to load platinum-based bimetallic. The preparation method uses a first electro-induced high temperature impact processing to prepare pure g-C3N4 powder, and through a second electro-induced high temperature impact processing, metal platinum and another metal atom are loaded on the pure g-C3N4 powder, and a bimetallic atomic catalytic system is used to make the bimetallic atoms cooperate with each other, improve the catalytic activity of g-C3N4, and broaden specific bifunctional catalytic sites; at the same time, the amount of precious metal loading is reduced, and a high-performance atomic platinum-based photocatalyst is reasonably constructed, so as to achieve the purpose of low-cost and high-efficiency photocatalytic water decomposition to produce hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a g-C3N4-loaded platinum-based bimetallic catalytic composite material and a preparation method thereof. Background Art

[0002] Photocatalytic hydrogen production technology using semiconductor photocatalysts is one of the most promising strategies to solve the global energy shortage. Graphitic carbon nitride (g-C3N4) is a semiconductor catalyst. Due to its advantages such as easy preparation, high stability, low price and environmental friendliness, it is considered to be one of the most promising photocatalytic water decomposition hydrogen production catalysts. However, g-C3N4 still has the disadvantages of poor charge transfer characteristics and low electron-hole recombination rate, which greatly limits the catalytic activity of g-C3N4.

[0003] To overcome this limitation, different strategies have been developed to modify g-C3N4 by depositing other types of atoms on it to improve its catalytic activity. The main methods include: (1) thermal polymerization: copolymerization of metal precursor materials and g-C3N4 can produce single-atom metal on the surface of g-C3N4; however, during the heating process of thermal polymerization, it is often necessary to maintain high temperature conditions for a long time, resulting in excessive energy consumption; (2) photochemical reduction: by long-term ultraviolet light irradiation, the metal ions in the metal precursor solution are reduced to metal elements and deposited on g-C3N4; this method is generally used for the deposition of precious metal platinum, and its application range is very narrow. In addition, the deposition by this method often has the problem of uneven distribution of metal atoms; (3) microwave radiation: the precursor is placed in a sample chamber filled with the desired deposition gas. Through short-term microwave radiation, the deposition gas ions repeatedly oscillate and collide with each other under the action of the microwave electromagnetic field, and the kinetic energy is finally converted into heat energy to obtain the desired product. The microwave radiation method has a fast reaction and high yield, but it also has the limitation of being difficult to control the thickness and load of single metal atoms. Therefore, there is an urgent need to develop a method that can quickly and efficiently prepare low-cost, high-efficiency, and high-activity catalytic materials to meet the needs of hydrogen energy production and utilization. Summary of the invention

[0004] The purpose of the present invention is to propose a g-C3N4-loaded platinum-based bimetallic catalytic composite material to solve the problem of low catalytic activity of the above-mentioned g-C3N4. The purpose of the present invention is also to propose a g-C3N4-loaded platinum-based bimetallic catalytic composite material to solve the problem of high cost and low efficiency of existing g-C3N4 modification methods.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material, which comprises the following steps:

[0007] S1: preparing a platinum precursor solution;

[0008] S2: dispersing metal salt powder in deionized water to obtain a metal salt dispersion;

[0009] S3: Mixing melamine powder with deionized water to form a thick mixture;

[0010] S4: After the thick mixture is evacuated, it is subjected to the first electrothermal impact processing. After the obtained product is cooled, it is taken out, ground and purified to obtain pure g-C3N4 powder;

[0011] S5: mixing the metal platinum precursor solution of step S1 with the metal salt dispersion of step S2 to obtain a mixed solution;

[0012] S6: Take the mixed liquid of step S5, drop it into the g-C3N4 powder obtained in step S4, mix them evenly, and perform a second electro-induced high temperature impact processing after vacuuming to obtain a g-C3N4-loaded platinum-based bimetallic catalytic composite material.

[0013] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, in step S1, the metal platinum precursor solution is chloroplatinic acid, and the preparation step of the metal platinum precursor solution includes: dissolving chloroplatinic acid hexahydrate in deionized water to obtain chloroplatinic acid.

[0014] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, in step S2, the metal salt powder includes one of a readily soluble chloride salt and a readily soluble nitrate salt.

[0015] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, the cation of the metal salt powder includes one of copper and nickel.

[0016] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, the mass ratio of the metal salt powder to the deionized water substance is 0.4 to 0.6.

[0017] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, the mass of the melamine powder is 1000-1500 mg, and the mass ratio of the melamine powder to deionized water is (1-2):(1-2).

[0018] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, in the step S4, the mixture is subjected to the first electro-induced high-temperature impact processing in a vacuum environment, the current passed through the viscous mixture is 80-120A, the voltage is 30-50V, and the processing temperature is 600-650°C; a continuous heating process and a cooling process are used as a heating cycle, the processing time and the cooling time are both in the range of 3-5s, and the heating cycle is repeated 2-5 times.

[0019] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, in step S5, when the metal platinum precursor solution and the metal salt dispersion are mixed, the volume ratio of the metal platinum precursor solution to the metal salt dispersion is (1 to 2): (1 to 2).

[0020] In the preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material, in the step S6, the volume of the mixed liquid is 150-300uL, and the mass of the g-C3N4 powder is 100-200mg; the current passed through the g-C3N4 powder in the second electro-high temperature impact processing is 80-120A, the voltage is 30-50V, and the processing temperature is 600-650°C; a continuous heating process and a cooling process are used as a heating cycle, the processing time and the cooling time are both 4-6s, and the heating cycle is repeated 2-5 times.

[0021] The present invention also provides a g-C3N4-loaded platinum-based bimetallic catalytic composite material, which is prepared by the above-mentioned method for preparing the g-C3N4-loaded platinum-based bimetallic catalytic composite material.

[0022] A technical solution in the present invention can have the following beneficial effects:

[0023] The preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material uses the first electrothermal shock processing to prepare pure g-C3N4 powder. During the first electrothermal shock processing, the processing temperature is controllable, thereby avoiding the decomposition of the target product caused by material instability. At the same time, the processing temperature can be adjusted according to actual conditions, expanding the application scope of the preparation method.

[0024] Moreover, the preparation method loads metal platinum and another metal atom on pure g-C3N4 powder through a second electro-induced high-temperature impact processing, and utilizes a bimetallic atomic catalytic system to make the bimetallic atoms cooperate with each other, thereby improving the catalytic activity of g-C3N4 and broadening specific bifunctional catalytic sites; at the same time, the loading amount of precious metals is reduced, and a high-performance atomic platinum-based photocatalyst is rationally constructed, thereby achieving the purpose of low-cost and high-efficiency photocatalytic water decomposition to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the cumulative hydrogen production of Example 1 and Comparative Examples 1 to 5 as photocatalysts in the photocatalytic hydrogen production experiment;

[0026] Figure 2 It is a schematic diagram of the average hydrogen production rate of Example 1 and Comparative Examples 1 to 5 as photocatalysts in the photocatalytic hydrogen production experiment. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is further illustrated by specific embodiments below. In order to facilitate understanding of the present invention, the present invention is described more comprehensively below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0028] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0030] The present invention provides a method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material, which comprises the following steps:

[0031] S1: preparing a platinum precursor solution;

[0032] S2: dispersing metal salt powder in deionized water to obtain a metal salt dispersion;

[0033] S3: Mixing melamine powder with deionized water to form a thick mixture;

[0034] S4: After the thick mixture is evacuated, it is subjected to the first electrothermal impact processing. After the obtained product is cooled, it is taken out, ground and purified to obtain pure g-C3N4 powder;

[0035] S5: mixing the metal platinum precursor solution of step S1 with the metal salt dispersion of step S2 to obtain a mixed solution;

[0036] S6: Take the mixed liquid of step S5, drop it into the g-C3N4 powder obtained in step S4, mix them evenly, and perform a second electro-induced high temperature impact processing after vacuuming to obtain a g-C3N4-loaded platinum-based bimetallic catalytic composite material.

[0037] The preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material uses the first electrothermal shock processing to prepare pure g-C3N4 powder. During the first electrothermal shock processing, the processing temperature is controllable, thereby avoiding the decomposition of the target product caused by material instability. At the same time, the processing temperature can be adjusted according to actual conditions, expanding the application scope of the preparation method.

[0038] Moreover, the preparation method loads metal platinum and another metal atom on pure g-C3N4 powder through a second electro-induced high-temperature impact processing, and utilizes a bimetallic atomic catalytic system to make the bimetallic atoms cooperate with each other, thereby improving the catalytic activity of g-C3N4 and broadening specific bifunctional catalytic sites; at the same time, the loading amount of precious metals is reduced, and a high-performance atomic platinum-based photocatalyst is rationally constructed, thereby achieving the purpose of low-cost and high-efficiency photocatalytic water decomposition to produce hydrogen.

[0039] Electrothermal impact machining is a method of controlling the temperature of the reaction position by adjusting discharge parameters such as discharge current, discharge voltage, etc. In a specific embodiment of the present invention, both the first electrothermal impact machining and the second electrothermal impact machining are performed using a current pulse machining device.

[0040] Specifically, in step S1, the metal platinum precursor solution is chloroplatinic acid, and the step of preparing the metal platinum precursor solution includes: dissolving chloroplatinic acid hexahydrate in deionized water to obtain chloroplatinic acid.

[0041] At present, precious metal platinum is the choice of more effective catalyst-supported metal, and the platinum element in chloroplatinic acid exists in the form of Pt4+, which is easy to lose ions under reducing conditions, so that it is reduced to metal nanoparticles; and water solubility is crucial for controlling reaction conditions during catalyst preparation because it can provide better controllability. In a specific embodiment of the present invention, 100-200 mg of hexahydrate chloroplatinic acid is dissolved in 1 mL of deionized water to prepare chloroplatinic acid. Under this parameter configuration, the deposition amount of platinum metal is 0.5-2wt%.

[0042] Furthermore, in step S2, the metal salt powder includes one of a soluble chloride salt and a soluble nitrate salt.

[0043] Compared with pure supported platinum metal systems, platinum-based bimetallic systems exhibit higher catalytic activity and selectivity. In addition, bimetallic catalysts have unique photoelectric properties, which are conducive to improving atomic cooperation and broadening specific bifunctional catalytic sites. Platinum-based bimetallic catalytic materials can reduce the use of Pt precious metals and save preparation costs, while improving effective atomic utilization and enhancing the catalytic system of metal atom deposition by exposing abundant active sites, and platinum atoms have metal synergistic effects in a low-coordination environment.

[0044] Furthermore, the cation of the metal salt powder includes one of copper and nickel.

[0045] In some specific embodiments of the present invention, the metal salt powder uses one of CuCl2, Cu(NO3)2 and NiSO4. Considering the advantages of atomic bimetallic dispersion, Cu is introduced into the photocatalyst of the single-atom Pt system to obtain a Pt-Cu diatomic pair, and the synergistic effect of the dimetallic atoms is used to improve the unit mass activity of Pt and optimize the catalytic activity. Copper is cheap, environmentally friendly and easy to synthesize, so the Pt-Cu dimetallic atomic pair is selected to solve the problem of the cost of preparing precious metal catalysts and improve the catalytic activity.

[0046] The preparation method of the g-C3N4-loaded platinum-based bimetallic catalytic composite material meets the deposition requirements of stable isolated Pt and Cu forms, forming atomically dispersed Pt-Cu bimetallic single atoms. The aggregation of metal atoms on the surface of g-C3N4 is avoided, resulting in a decrease in the specific surface area of ​​the photocatalyst, and only the surface of the metal clusters plays a catalytic role, resulting in a significant reduction in the unit efficiency of the catalyst.

[0047] Similarly, introducing nickel into the single-atom Pt system photocatalyst can also solve the cost problem of preparing precious metal catalysts and improve the catalytic activity.

[0048] Specifically, the mass ratio of the metal salt powder to the deionized water is 0.4 to 0.6.

[0049] The mass ratio of metal salt powder to deionized water is set according to the target deposition amount, and the deposition amount of other metals should be 2-3wt%. If the deposition amount is too small, the catalytic material prepared finally will have fewer catalytic active sites, affecting the catalytic rate; if the deposition amount is too high, metal particles will inevitably accumulate, reducing the specific surface area of ​​the catalytic material and reducing the reaction rate.

[0050] Specifically, the mass of the melamine powder is 1000-1500 mg, and the mass ratio of the melamine powder to deionized water is (1-2):(1-2).

[0051] The deionized water mixed with the melamine powder plays a role in wrapping and fixing the melamine powder. In a specific embodiment of the present invention, the mass ratio of melamine powder to deionized water is 1:1. During the first electrical high temperature shock, a large amount of energy is generated at the moment of the shock. If too little deionized water is added, the powder will escape, resulting in a large loss; if too much deionized water is added, the mixture will be in a flowable liquid state instead of a thick state, which will result in a long processing time and affect the processing efficiency.

[0052] Specifically, in step S4, the mixture is subjected to the first electrothermal high temperature impact processing in a vacuum environment, the current passed through the viscous mixture is 80-120A, the voltage is 30-50V, and the processing temperature is 600-650°C; a continuous heating process and a cooling process are a heating cycle, the processing time and the cooling time are both in the range of 3-5s, and the heating cycle is repeated 2-5 times.

[0053] By using the electrothermal impact processing method, a shorter temperature change can be achieved. The ultra-short processing time can not only ensure the high quality of the product, but also make the synthesis process more efficient and require less energy consumption. Through the above-mentioned first electrothermal impact processing, impurities and oxides of g-C3N4 powder can be removed, thereby obtaining a high-purity graphite phase carbon nitride material. The prepared pure g-C3N4 powder is light yellow.

[0054] Specifically, in step S5, when the metal platinum precursor solution and the metal salt dispersion are mixed, the volume ratio of the metal platinum precursor solution to the metal salt dispersion is (1-2):(1-2).

[0055] In a preferred embodiment of the present invention, the volume ratio of the metal platinum precursor solution to the metal salt dispersion is 1: 1. With the above ratio, the metal platinum and another metal are loaded on g-C3N4 in a ratio of 1: 1, which can improve the unit mass activity of the metal platinum, solve the cost problem of the preparation of the precious metal catalyst, and optimize the catalytic activity of the photocatalyst.

[0056] Specifically, in the step S6, the volume of the mixed liquid is 150-300uL, and the mass of the g-C3N4 powder is 100-200mg; the current passed through the g-C3N4 powder in the second electrothermal high temperature impact processing is 80-120A, the voltage is 30-50V, and the processing temperature is 600-650℃; a continuous heating process and a cooling process are a heating cycle, the processing time and the cooling time are both 4-6s, and the heating cycle is repeated 2-5 times.

[0057] The mixed solution is added to the g-C3N4 powder and mixed evenly, and then an electric current is passed through the g-C3N4 powder mixed with the mixed solution to place the g-C3N4 powder in a high temperature environment. A continuous heating process and a cooling process are considered as one cycle, and the number of cycles is 2 to 5 times.

[0058] By combining the above processing method with vacuum annealing, high temperature is first used to achieve the growth of metal atoms, and then vacuum annealing is performed to make the metal atoms have a relatively uniform size and distribution, thereby achieving the deposition of metal atoms on the g-C3N4 surface, avoiding the problem of local accumulation and uneven size of metal atoms in traditional processing methods.

[0059] The present invention also provides a g-C3N4-loaded platinum-based bimetallic catalytic composite material, which is prepared by the above-mentioned method for preparing the g-C3N4-loaded platinum-based bimetallic catalytic composite material.

[0060] The g-C3N4-loaded platinum-based bimetallic catalytic composite material is prepared by combining metal platinum with other metal atoms and loading them onto g-C3N4; utilizing a bimetallic atomic catalytic system to enable the bimetallic atoms to cooperate with each other, thereby improving the catalytic activity and broadening specific bifunctional catalytic sites; and at the same time, reducing the amount of precious metal loading, rationally constructing a high-performance atomic platinum-based photocatalyst, and achieving the purpose of low-cost and high-efficiency photocatalytic water splitting to produce hydrogen.

[0061] Example 1

[0062] A method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material comprises the following steps:

[0063] 100 mg of chloroplatinic acid hexahydrate was dissolved in 1 mL of deionized water, and the mixture was mixed to obtain a metal platinum precursor solution;

[0064] Take 10 mg of CuCl2 as the precursor metal salt of the target metal Cu and dissolve it in 25 mL of deionized water to obtain a CuCl2 metal salt dispersion;

[0065] Take 1000 mg of melamine powder and mix it with 1 mL of deionized water to form a thick mixture;

[0066] The thick mixture is placed in an electric pulse processing device, and after vacuuming, the first electric high temperature impact processing is performed. The current of the first electric high temperature impact processing is 100A, the voltage is 40V, and the processing temperature is 625°C; a continuous heating process and a cooling process are a heating cycle, the processing time and the cooling time range are both 5s, and the heating cycle is repeated 5 times; after the obtained product is cooled, it is taken out, ground and purified to obtain pure g-C3N4 powder;

[0067] Take 150uL of the above-mentioned metal platinum precursor solution and the above-mentioned CuCl2 metal salt dispersion, mix them evenly, and obtain a mixed solution;

[0068] Take 300uL of the above-mentioned mixed liquid and 200mg of the above-mentioned g-C3N4 powder, drop them into the above-mentioned g-C3N4 powder, and mix them evenly; then, put the g-C3N4 powder mixed with the mixed liquid into the current pulse processing equipment, evacuate and perform the second electric high-temperature impact processing; the current of the second electric high-temperature impact processing is 100A, the voltage is 40V, and the processing temperature is 625℃; a continuous heating process and a cooling process are used as a heating cycle, the processing time and the cooling time range are both 5s, and the heating cycle is repeated 5 times; obtain the g-C3N4-loaded platinum-based bimetallic catalytic composite material.

[0069] Comparative Example 1

[0070] The preparation steps of Comparative Example 1 are basically the same as those of Example 1, except that Comparative Example 1 does not include the step of preparing a metal salt dispersion and the step of mixing a metal platinum precursor solution with the metal salt dispersion; the specific parameters of other steps are the same as those of Example 1; Comparative Example 1 only uses a metal platinum precursor solution to drop into the g-C3N4 powder, and performs a second electro-induced high-temperature impact processing to prepare a composite catalytic material of g-C3N4 loaded with a single platinum atom.

[0071] Comparative Example 2

[0072] The preparation steps of Comparative Example 2 are basically the same as those of Example 1, except that Comparative Example 2 does not include the step of preparing a metal platinum precursor solution and the step of mixing the metal platinum precursor solution with the metal salt dispersion; the specific parameters of the other steps are the same as those of Example 1; Comparative Example 1 only uses metal salt dispersion drops to be dropped into g-C3N4 powder, and performs a second electro-induced high temperature impact processing to prepare a composite catalytic material of copper single atom loaded g-C3N4.

[0073] Comparative Example 3

[0074] Take 1000 mg of melamine powder and mix it with 1 mL of deionized water to form a thick mixture;

[0075] The thick mixture is placed into an electric current pulse processing device, and after vacuuming, electric high temperature impact processing is performed. The current of the electric high temperature impact processing is 100A, the voltage is 40V, the processing temperature is 625°C, the processing time and cooling time are both in the range of 5s, and the number of cycles is 5 times; after the obtained product is cooled, it is taken out, ground and purified to obtain pure g-C3N4 powder.

[0076] Comparative Example 4

[0077] A method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material comprises the following steps:

[0078] 100 mg of chloroplatinic acid hexahydrate was dissolved in 1 mL of deionized water, and the mixture was mixed to obtain a metal platinum precursor solution;

[0079] Take 10 mg of CuCl2 as the precursor metal salt of the target metal Cu and dissolve it in 25 mL of deionized water to obtain a CuCl2 metal salt dispersion;

[0080] Take 1000 mg of melamine powder and mix it with 1 mL of deionized water to form a thick mixture;

[0081] The thick mixture is placed in an electric pulse processing device, and after vacuuming, the first electric high temperature impact processing is performed. The current of the first electric high temperature impact processing is 100A, the voltage is 40V, and the processing temperature is 625°C; a continuous heating process and a cooling process are a heating cycle, the processing time and the cooling time range are both 5s, and the heating cycle is repeated 5 times; after the obtained product is cooled, it is taken out, ground and purified to obtain pure g-C3N4 powder;

[0082] Take 150uL of the above-mentioned metal platinum precursor solution and the above-mentioned CuCl2 metal salt dispersion, mix them evenly, and obtain a mixed solution;

[0083] Take 300uL of the mixed solution and 200mg of the above g-C3N4 powder and add them dropwise into a beaker of 100mL containing 50mL. Stir for 30min under irradiation with a 300W xenon lamp to obtain a g-C3N4-loaded platinum-based bimetallic catalytic composite material prepared by photodeposition method.

[0084] Comparative Example 5

[0085] The preparation steps of Comparative Example 5 are the same as those of Example 1, except that, in the first electrothermal shock processing and the second electrothermal shock processing of Comparative Example 5, a continuous heating process and a cooling process are used as a heating cycle, the processing time and the cooling time range are both 10 seconds, and the heating cycle is repeated 5 times;

[0086] Photocatalytic hydrogen production experiment:

[0087] 20 mg of the photocatalytic materials prepared in the embodiment of the present invention, comparative example 1, comparative example 2, comparative example 3, comparative example 4 and comparative example 5 were taken respectively, added to a quartz reaction dish filled with 90 mL of deionized water, and 10 vol% triethanolamine (TEOA) was added as a sacrificial agent to provide sufficient electrons for photocatalytic water decomposition, thereby promoting the redox reaction of water decomposition; before the reaction started, nitrogen was introduced into the reaction dish to discharge the gas therein to prevent the gas in the solution system from affecting subsequent experiments. During the experiment, the volume data of hydrogen produced was collected every 1 hour to obtain the hydrogen production rate of each photocatalytic material.

[0088] The schematic diagram of the cumulative hydrogen production and the schematic diagram of the average hydrogen production rate of the prepared photocatalytic materials as photocatalysts in the embodiment of the present invention, comparative example 1, comparative example 2, comparative example 3, comparative example 4 and comparative example 5 in the photocatalytic hydrogen production experiment are shown in the attached drawings respectively. Figure 1 and Figure 2 shown.

[0089] In Comparative Example 1, no metal salt dispersion was added, and a composite catalytic material of g-C3N4 loaded with single platinum atoms was prepared. In Comparative Example 2, no metal platinum precursor solution was added, and a composite catalytic material of g-C3N4 loaded with single copper atoms was prepared. Comparative Example 3 is pure g-C3N4, which is a blank control. It can be seen from Example 1 and Comparative Examples 1 to 3 that the photocatalytic performance of the g-C3N4 loaded platinum-based bimetallic catalytic composite material is better than that of the composite catalytic material loaded with only single copper atoms or only single platinum atoms.

[0090] By comparing Example 1 with Comparative Example 4, it can be seen that the catalytic effect of the g-C3N4-loaded platinum-based bimetallic catalytic composite material prepared by the photodeposition method is worse than the catalytic effect of the g-C3N4-loaded platinum-based bimetallic catalytic composite material obtained by electro-induced high temperature impact processing.

[0091] By comparing Example 1 with Comparative Example 5, it can be seen that the annealing parameters have a great influence on the metal deposition effect. An inappropriate annealing time leads to poor metal dispersion or deposition effect, affecting the quality of the catalytic material.

[0092] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific embodiments of the present invention without creative work, and these equivalent variations or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material, characterized in that: It includes the following steps: S1: preparing a platinum precursor solution; S2: dispersing metal salt powder in deionized water to obtain a metal salt dispersion; S3: Mixing melamine powder with deionized water to form a thick mixture; S4: After the thick mixture is evacuated, it is subjected to the first electrothermal impact processing. After the obtained product is cooled, it is taken out, ground and purified to obtain pure g-C3N4 powder; S5: mixing the metal platinum precursor solution of step S1 with the metal salt dispersion of step S2 to obtain a mixed solution; S6: taking the mixed solution of step S5, dropping it into the g-C3N4 powder obtained in step S4, and mixing them evenly, and performing a second electric high temperature impact processing after vacuuming to obtain a g-C3N4-supported platinum-based bimetallic catalytic composite material; Wherein, in the step S5, when the metal platinum precursor solution and the metal salt dispersion are mixed, the volume ratio of the metal platinum precursor solution to the metal salt dispersion is (1-2):(1-2); in the step S6, the volume of the mixed solution is 150-300uL, and the mass of the g-C3N4 powder is 100-200mg; the current passed to the g-C3N4 powder in the second electro-high temperature impact processing is 80-120A, the voltage is 30-50V, and the processing temperature is 600-650°C; a continuous heating process and a cooling process are a heating cycle, the processing time and the cooling time are both 4-6s, and the heating cycle is repeated 2-5 times.

2. The method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material according to claim 1, characterized in that: In step S1, the metal platinum precursor solution is chloroplatinic acid, and the preparation step of the metal platinum precursor solution includes: dissolving chloroplatinic acid hexahydrate in deionized water to obtain chloroplatinic acid.

3. The method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material according to claim 1, characterized in that: In the step S2, the metal salt powder includes one of a soluble chloride salt and a soluble nitrate salt.

4. The method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material according to claim 3, characterized in that: The cation of the metal salt powder includes one of copper and nickel.

5. The method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material according to claim 1, characterized in that: The mass ratio of the metal salt powder to the deionized water is 0.4 to 0.

6.

6. The method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material according to claim 1, characterized in that: The mass of the melamine powder is 1000-1500 mg, and the mass ratio of the melamine powder to deionized water is (1-2):(1-2).

7. The method for preparing a g-C3N4-supported platinum-based bimetallic catalytic composite material according to claim 1, characterized in that: In step S4, the mixture is subjected to the first electrothermal high temperature impact processing in a vacuum environment, the current passed into the viscous mixture is 80-120A, the voltage is 30-50V, and the processing temperature is 600-650°C; a continuous heating process and a cooling process are considered as a heating cycle, the processing time and the cooling time are both in the range of 3-5s, and the heating cycle is repeated 2-5 times.

8. A g-C3N4-supported platinum-based bimetallic catalytic composite material, characterized in that: The g-C3N4-loaded platinum-based bimetallic catalytic composite material is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Metal / graphite-like carbon nitride compound catalyst and preparing method thereof

    CN103586064A

  • Preparation method of copper-platinum bi-metal carrying carbon nitride nanotube

    CN110116017A

  • Method for synthesizing carbon-supported monatomic catalyst by thermal shock and carbon-supported monatomic catalyst

    CN113151861A

  • Preparation method of bimetallic monatomic modified semiconductor photocatalyst for producing hydrogen by photolysis of water

    CN115041210A

  • Method for preparing g-C3N4 loaded Pt composite material

    CN117225441A